1987
DOI: 10.1093/carcin/8.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Separation by ion-pair high-performance liquid chromatography of the glucuronide, sulfate and glutathione conjugates formed from benzo[a]pyrene in cell cultures from rodents, fish and humans

Abstract: A large proportion of the metabolites formed from benzo[a]pyrene (BP) in cell cultures from rodents, fish and humans result from conjugation of an oxidized metabolite of BP with sulfate, glucuronic acid or glutathione (GSH). To improve the analysis of these metabolites, a reversed-phase ion-pair h.p.l.c. system using a step gradient of methanol:tetrabutyl-ammonium bromide in ammonium formate buffer has been developed for the separation of these three classes of conjugates. This system separated 3-hydroxy-BP gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…HPLC using a reversed-phase column with ion pairing has been used with numerous aromatic/aliphatic hydrocarbon epoxide-derived glutathione conjugates (Hernandez et al, 1980;Armstrong et al, 1981;Steele et al, 1981;Plakunov et al, 1987). Ion-exchange columns have proven effective in the isolation of conjugates derived from dichloroethylene (Dowsley et al, 1995), 4-ipomeanol (Buckpitt and Boyd, 1980), or benzo(a)pyrene (Jernstrom et al, 1982).…”
Section: Measurement Of Glutathione Conjugatesmentioning
confidence: 99%
“…HPLC using a reversed-phase column with ion pairing has been used with numerous aromatic/aliphatic hydrocarbon epoxide-derived glutathione conjugates (Hernandez et al, 1980;Armstrong et al, 1981;Steele et al, 1981;Plakunov et al, 1987). Ion-exchange columns have proven effective in the isolation of conjugates derived from dichloroethylene (Dowsley et al, 1995), 4-ipomeanol (Buckpitt and Boyd, 1980), or benzo(a)pyrene (Jernstrom et al, 1982).…”
Section: Measurement Of Glutathione Conjugatesmentioning
confidence: 99%
“…Diamond et al (1968), Diamond and Gelboin (1969), and Gelboin et al (1972) showed that only those cultured mammalian cells lacking constitutive AHH activity were resistant to B[a]P, as cytotoxicity was dependent on the bioconversion of B[a]P to active metabolites. HepG2 cells possess AHH activity (Sassa et al, 1987) and can metabolize B[a]P (Diamond et al, 1980;Plakunov et al, 1987). The sensitivity of the HepG2 cells to B[a]P apparently reflected their ability to metabolize B[a]P to cytotoxic products, as sensitivity to B[a]P was pronounced in Arochlor-induced cells and was reduced in t~-naphthoflavone-treated cells.…”
Section: Studies With B[a]pmentioning
confidence: 99%
“…The HepG2 cell line has been well characterized and produces most of the plasma proteins and has biosynthetic capabilities similar to those of normal human hepatocytes (Aden et al, 1979Rash et al, 1981;Tam et al, 1985). Of importance for use in in vitro cytotoxicity assays is that the HepG2 cells have retained some of the drugmetabolizing capacity of normal hepatocytes (Diamond et al, 1980;Plakunov et al, 1987;Sassa et al, 1987) which can be increased by culturing the cells in the presence of inducers, such as benzo[a]anthracene (B[a]A), 3-methylcholanthrene (3-MC), and Arochlor (Dawson et al, 1985;Bhatt, 1986;Marselos et al, 1987). Although the HepG2 cells have been used for assessments of the genotoxicity of test agents that require metabolic activation (Diamond et al, 1980;Bhatt et al, 1983;Dearfield et al, 1983Dearfield et al, , 1985Buenaventura et al, 1984;Dawson et al, 1985;Bhatt, 1986;Grady et al, 1986;Zhou et al, 1986;Eddy et al, 1987), similar applications to in vitro cytotoxicity tests have not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…BaP is also found in ambient (outdoor) air, indoor air, and in some water sources (U.S. Environmental Protection Agency, 2005). Many of PAH compounds including B[a]P have been shown to be toxic, mutagenic and/or carcinogenic by extensive experiments in vivo (Harvey, 1985;Plakunov et al, 1987;Hawkins et al, 1990) and in vitro (Elhassaneen, 1996;Elhassaneen et al, 1997;and Elhassaneen, 2002) systems. Also, B[a]P exposure is associated with the development of liver toxicity and carcinogenicity in mammals, rodent and fish (Harvey, 1985and Hawkins et al, 1988Elhassaneen, 1996 andElhassaneen, 2002).…”
Section: Introductionmentioning
confidence: 99%